Addressing Empathic Failures. (December 2015) - Zaki, Jamil; Cikara, Mina
Empathy is critical for social functioning, but it often wanes when it is needed most. Resulting empathic failures precipitate and worsen social conflict. Accordingly, conflict-reduction interventions prioritize developing empathy in order to achieve harmony. Recent research has indicated that such interventions can benefit from a more nuanced understanding of empathy. First, empathy is a multidimensional construct, including understanding, sharing, and feeling concern for others' emotions. The expression of these empathic processes is further influenced by psychological factors that "tune" people toward or away from empathy. Interventions must therefore diagnose the specific nature and precursors of empathic failures and tailor interventions appropriately. Second, empathy alone may be insufficient to produce prosocial behavior, especially when parties differ in status or power. In these cases, interventions should promote equitable goals and norms in addition to empathy. By understanding its component processes and boundary conditions, practitioners can work to promote empathy in maximally effective ways.